Locked-on vortex shedding modes from a rotationally oscillating circular cylinder. (1st December 2017) - Mittal, H.V.R.; Al-Mdallal, Qasem M.; Ray, Rajendra K.
Abstract: Numerical simulations of unsteady two-dimensional flow around a rotationally oscillating circular cylinder, placed in a uniform cross flow of a constant property Newtonian fluid, are performed at a fixed Reynolds number of 200. The investigation is based on the solutions of stream function-vorticity formulation of Navier-Stokes equations on non-uniform polar grids using a higher order compact (HOC) formulation. The flow field is mainly influenced by Reynolds number, R e, maximum angular velocity of the cylinder, α m, and the frequency ratio, f / f 0, which represents the ratio between the frequency of oscillation, f, and the natural vortex shedding frequency, f 0 . The ranges considered for these parameters are 0.5 ⩽ α m ⩽ 6.0 and 0.5 ⩽ f / f 0 ⩽ 3.0 . The resulting vortex formation modes and lock-on phenomena behind the cylinder as well as the fluid forces acting on the cylinder are analyzed. Occurrence of new multiple lock-on regions is demonstrated in detail by the variation of f and α m . The instances of high drag reduction at high values of α m are confirmed. Comparisons with previous numerical and experimental results verify the accuracy and validity of the present study. Highlights: The problem of a cylinder undergoing controlled rotational oscillations in a uniform stream is numerically investigated. Different locked-on vortex shedding modes are observed when either oscillation amplitude or forcing frequency increases. The occurrence of multiple lock-on regions is demonstrated. The effect of controlled rotational oscillation cylinder in reducing the drag is discussed.